The enhanced immunological activity of Paulownia tomentosa flower polysaccharide on Newcastle disease vaccine in chicken. Issue 5 (3rd May 2019) - Yang, Haifeng; Zhang, Ping; Xu, Xiaozhou; Chen, Xiaolan; Liu, Qingxin; Jiang, Chunmao
Abstract : The extracts of Paulownia tomentosa ( P. tomentosa ) exhibit multiple pharmacological activities. In the present study, P. tomentosa flower polysaccharides (PTFP) were extracted by water decoction and ethanol precipitation, and the immunologic modulations of PTFP against Newcastle disease (ND) vaccine was investigated in chickens. The results showed that in a certain range of concentrations, PTFP treatment can dose-dependently enhance lymphocyte proliferation. Then, 280 14-days-old chickens were randomly divided into seven groups, and vaccinated with ND vaccine except blank control (BC) group. At the first vaccination, chickens were orally administrated with PTFP at concentration ranging from 0 to 50 mg/kg once a day for 3 successive days, and the BC group was treated with physiological saline. The lymphocyte proliferation rate, serum antibody titer, and levels of interferon-γ (IFN-γ) were respectively measured on 7, 14, 21, and 28 days after the first vaccination. The results showed that PTFP at the suitable doses could significantly promote lymphocyte proliferation, enhance serum antibody titer, and improve serum IFN-γ concentrations. Taken together, these data indicated that PTFP could improve the immune efficacy against ND vaccine in chickens, and could be as the candidate of a new-type immune adjuvant.